α-Synuclein Heterocomplexes with β-Amyloid Are Increased in Red Blood Cells of Parkinson’s Disease Patients and Correlate with Disease Severity - Daniele, Simona; Frosini, Daniela; Pietrobono, Deborah; Petrozzi, Lucia; Lo Gerfo, Annalisa; Baldacci, Filippo; Fusi, Jonathan; Giacomelli, Chiara; Siciliano, Gabriele; Trincavelli, Maria Letizia; Franzoni, Ferdinando; Ceravolo, Roberto; et al. (Frontiers in Molecular Neuroscience, 2018)
Neurodegenerative disorders (NDs) are characterized by abnormal accumulation/misfolding of specific proteins, primarily -synuclein (-syn), -amyloid1-42 (A1-42) and tau, in both brain and peripheral tissues. In addition to oligomers, the role of the interactions of α-syn with A or tau has gradually emerged. Nevertheless, despite intensive research, NDs have no accepted peripheral markers for biochemical diagnosis. In this respect, Red Blood Cells (RBCs) are emerging as a valid peripheral model for the study of aging-related pathologies. Herein, a small cohort (N=28) of patients affected by Parkinson’s disease (PD) and age-matched controls were enrolled to detect the content of α-syn (total and oligomeric), Aβ1-42 and tau (total and phosphorylated) in RBCs. Moreover, the presence of α-syn association with tau and Aβ1-42 was explored by co-immunoprecipitation/western blotting in the same cells, and quantitatively confirmed by immunoenzymatic assays. For the first time, PD patients were demonstrated to exhibit α-syn heterocomplexes with Aβ1-42 and tau in peripheral tissues; interestingly, α-syn-Aβ concentrations were increased in PD subjects with respect to healthy controls, and directly correlated with disease severity and motor deficits. Moreover, total-α-syn levels were decreased in PD subjects and inversely related to their motor deficits. Finally, an increase of oligomeric-α-syn and phosphorylated-tau was observed in RBCs of the enrolled patients. The combination of three parameters (total-α-syn, phosphorylated-tau and α-syn-Aβ concentrations) provided the best fitting predictive index for discriminating PD patients from controls. Nevertheless further investigations should be required, overall, these data suggest α-syn hetero-aggregates in RBCs as a putative tool for the diagnosis of PD.